The role of primary caregivers’ knowledge, attitudes, and practices in paediatric medication safety - Thamodha Weerasinghe; Radeesha Dassanayake; Minoli Senapathy; Raveen Thennakoon; Kavinda Dayasiri (BMC Research Notes)
Abstract Objective To assess primary caregivers’ knowledge, attitudes, and practices (KAP) regarding the prevention of unintentional drug poisoning in children. Results Most primary caregivers (96.9%) were aware of drug overdose risks, and 85.5% understood variations in syrup strengths. However, only 44.9% knew the legal consequences of repeated poisonings. Unsafe practices were prevalent, with 37.7% administering medications without clinician consultation and 25.5% attempting to induce vomiting following poisoning. Among parent caregivers, the median knowledge score was 7 (IQR 6–8), and the median practice score was 13 (IQR 12–14). Higher parental knowledge significantly correlated with safer practices (p = 0.001) and positive attitudes (p = 0.02). However, attitudes (p = 0.880) and practices (p = 0.229) did not differ significantly between caregivers with and without prior poisoning experience. Despite high knowledge levels, unsafe practices remain common, highlighting the need for targeted interventions to improve practical skills and reduce childhood poisoning rates.